2022
DOI: 10.1021/acs.analchem.2c00165
|View full text |Cite
|
Sign up to set email alerts
|

Near-Infrared Photoacoustic Probe for Reversible Imaging of the ClO/GSH Redox Cycle In Vivo

Abstract: Homeostasis of the cellular redox status plays an indispensable role in diverse physiological and pathological processes. Hypochlorite anion (ClO–) and glutathione (GSH) represent an important redox couple to reflect the redox status in living cells. The current cellular redox probes that detect either ClO– or GSH alone are not accurate enough to monitor the real redox status. In this work, a reversible photoacoustic (PA) probe, DiOH-BDP, has been synthesized and applied for PA imaging to monitor the ClO–/GSH … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 34 publications
(13 citation statements)
references
References 47 publications
0
13
0
Order By: Relevance
“…Bioactive molecules such as proteins, microRNAs (miRNAs), and peptides, , as indispensable components of cells and tissues, play a crucial role in cell proliferation, tissue differentiation, and body metabolism. Studies have found that tumor progression and prognosis are accompanied by abnormal changes in the expression levels of more than one bioactive substance. For example, miRNAs are important regulators of most physiological processes, and their dysregulated expressions are related to cancer and other pathological diseases. Meanwhile, glutathione (GSH), as one of the most plentiful endogenous antioxidants against free radicals and toxins, has been shown to be significantly upregulated in various cancer cells. So far, various strategies have been reported for miRNA or GSH detection, such as CRISPR systems, colorimetry, the quantitative polymerase chain reaction, and fluorescence. However, these existing methods are usually restricted to the analysis of a single biomarker or the same type of different biomarkers, which could no longer meet the growing demand for the early ultrasensitive clinical diagnosis of cancer. Therefore, it is of great significance to develop an ultrasensitive biosensor to monitor different types of biomarkers and further provide more precise and comprehensive data guidance for cancer diagnosis and clinical decision making.…”
Section: Introductionmentioning
confidence: 99%
“…Bioactive molecules such as proteins, microRNAs (miRNAs), and peptides, , as indispensable components of cells and tissues, play a crucial role in cell proliferation, tissue differentiation, and body metabolism. Studies have found that tumor progression and prognosis are accompanied by abnormal changes in the expression levels of more than one bioactive substance. For example, miRNAs are important regulators of most physiological processes, and their dysregulated expressions are related to cancer and other pathological diseases. Meanwhile, glutathione (GSH), as one of the most plentiful endogenous antioxidants against free radicals and toxins, has been shown to be significantly upregulated in various cancer cells. So far, various strategies have been reported for miRNA or GSH detection, such as CRISPR systems, colorimetry, the quantitative polymerase chain reaction, and fluorescence. However, these existing methods are usually restricted to the analysis of a single biomarker or the same type of different biomarkers, which could no longer meet the growing demand for the early ultrasensitive clinical diagnosis of cancer. Therefore, it is of great significance to develop an ultrasensitive biosensor to monitor different types of biomarkers and further provide more precise and comprehensive data guidance for cancer diagnosis and clinical decision making.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, the injection of lipoic acid to regenerate GSH in ALI models attributed to the recovery of DiOH-BDP and led to the decrease in PA signal at 770 nm. As a result, PA signals at 770 nm can be explored for detecting ClO − /GSH by using DiOH-BDP in vitro and vivo [ 89 ].…”
Section: Small Molecular Organic Dye-based Pa Probesmentioning
confidence: 99%
“…), has attracted enormous research interest among molecular biological studies. This is because excessive oxidative small molecules can cause DNA damage and gene mutation, and play negative impacts on the modification process of protein in living organisms. , With the advantages of noninvasive, highly responsive, and real-time monitoring properties, fluorescent probes can be used for certain experimental detection/monitoring purposes of the as-mentioned oxidative small molecules in diverse complex systems, such as the recognition and real-time monitoring of ClO – (refs ) or H 2 O 2 . , Considering the complex environment in living organisms, one fluorescent probe must be optimized to meet the changes in diverse detection environments with superior data calibration or comparison methodology, and to determine/assess the content changes of active small molecules in both accurate detection in vitro and imaging in vivo, e.g., for the detection of biological samples or blood samples in vitro, fluorescent probes need achieve high response activity; meanwhile, for imaging in vivo, fluorescent probes that monitor the process of small molecule changes must show satisfactory tissue penetration depth and spatial resolution.…”
Section: Introductionmentioning
confidence: 99%